Systematic Literature Review (SLR) Evaluasi Kelembagaan Peternakan dengan Pendekatan Bibliometrik Menggunakan VOSviewer Berbasis PICOS dan PRISMA: Systematic Literature Review (SLR): An Institutional Evaluation of the Livestock Sector Using a Bibliometric Approach with VOSviewer Based on PICOS and PRISMA - Alvandika, Anas; Wakhidati, Yusmi Nur; Sugiarto, Mochamad (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Livestock institutions play a crucial role in supporting the sustainability of the livestock sector, yet they still face challenges such as institutional fragmentation, suboptimal coordination among stakeholders, and the pressures of climate change. This study aims to evaluate the strengthening of livestock institutions and its implications for sustainability and socio-economic aspects. The approach used is a bibliometric-based Systematic Literature Review (SLR) employing the PICOS framework, analyzing 125 articles from 2020 to early 2025 sourced from reputable journals, including Google Scholar. The selection process followed the PRISMA protocol, while bibliometric analysis was conducted using VOSviewer to identify patterns of interrelationships, clusters, and research trends. The analysis results revealed three main clusters: livestock production, livestock management and business, and institutional strengthening intersecting with sustainability aspects. The dominance of the production and management clusters indicates that institutional studies remain focused on technical and economic aspects, while the integration of sustainability dimensions is not yet optimal. Research gaps are evident in the limited studies on minor livestock such as sheep, as well as the lack of strong integration of digitalization and climate change adaptation issues. The low level of involvement of local actors, such as cooperatives and community-based organizations, also poses a challenge to institutional strengthening. A review of the literature confirms that effective institutional strengthening requires an inclusive, collaborative, and evidence-based approach, involving the strengthening of local institutional capacity and cross-sectoral integration. This approach is essential for accommodating commodity diversification, enhancing the resilience of the livestock system, and promoting sustainable, adaptive, and competitive livestock development.